Nanodrug Delivery Systems for Direct Clearance or Neutralization of LPS - Chen L; Pan R; Xu X; Guo J (International Journal of Nanomedicine)
Lu Chen,1 Ran Pan,1 Xiaoling Xu,2 Junping Guo1 1Rehabilitation and Nursing School, Hangzhou Vocational & Technical College, Hangzhou, Zhejiang, People’s Republic of China; 2Shulan International Medical College, Zhejiang Shuren University, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Xiaoling Xu, Shulan International Medical College, Zhejiang ShurenUniversity, Hangzhou, 310015, People’s Republic of China, Tel/Fax +86-571-88208435, Email ziyao1988@zju.edu.cn Junping Guo, Rehabilitation and Nursing School, Hangzhou Vocational & Technical College, Hangzhou, Zhejiang, 310018, People’s Republic of China, Tel/Fax +86-571-56700217, Email guojunping@hzvtc.edu.cnAbstract: Lipopolysaccharide (LPS) is a unique component of the outer wall of gram-negative bacteria and is a complex composed of lipids and polysaccharides. Normally, liver sinusoidal endothelial cells (LSECs) systemically clear LPS via unknown mechanisms. However, under pathological conditions, LPS causes lethal endotoxemia if it cannot be rapidly cleared from the blood circulation. Currently, an increasing number of drugs have demonstrated the ability to clear or neutralize LPS. However, due to their inherent characteristics, such as low biocompatibility and short half-life, their clinical applications are limited. Nanodrug delivery systems have the advantages of improving pharmacokinetics, increasing bioavailability, reducing the occurrence of side effects, and prolonging drug circulation time, which can compensate for the shortcomings of traditional drugs. This review summarizes nanodrug delivery systems that can clear or neutralize LPS, such as polymer nanodrug delivery systems, lipid-based nanodrug delivery systems, peptide-based nanodrug delivery systems, inorganic nanodrug delivery systems, nanosponges, and extracellular vesicles, which provides an outlook on the application and future prospects of nanodrug delivery systems for clearing and neutralizing LPS. Keywords: nanodrug delivery system, LPS clearance, LPS neutralization, inflammation, nanomaterial